Organic Matter and Phosphorus Fertilizer Application to Sustain Maize Growth under Water Stress Condition in Calcareous Soil - Utami, Sri Rahayu; Rohmawatia, H.; Kumalontang, W. J. N.; Prijono, Sugeng (KnE Life Sciences, 2017)
Crop growth is normally rather limited in calcareous soils, due to the low phophorus availability and water scarcity. Organic matter (OM) is commonly applied to reduce P fixation, as also improving other nutrients content and water availability in the soil. Since calcareous soils often encounter water scarcity especially in dry period, the effectiveness of OM under water stress condition is still interesting to study. An incubation experiment was conducted to study the effect of water stress, P-fertilizer and organic matter application on P-uptake and maize growth in calcareous soil. Soil samples used for this study, were taken from 0-20 cm depth, in Pagak, South Malang, East Java. A complete randomized design was used, with 3 factors and 3 replications. Factor 1 was consisted of 3 water stress level, i.e no stress (S0), slightly stress (S1), and moderately stress (S2). Factor 2 was consisted of 2 Phosphorus level: with (200 kg SP36 per Ha). and without P-fertilizer. Factor 3 was OM application (12 Mg Ha-1), i.e. without OM (B0), Tithonia diversifolia (B1), Gliricidia sepium (B2), and combination of Tithonia diversifolia and Gliricidia sepium (B3).Soil samples were added with fertilizer and organic matter, and incubated within 2 weeks. Water stress treatment were conducted after incubation period. Phosphorus availability (P-Olsen and P-labile) in the soil was measured at 0, 28, and 56 day after planting (dap). Crop height was measured at 14, 28, 42, and 56 dap. Whereas P-uptake and biomass dry weight were measured at 56 dap. The results showed that OM application increased P-uptake, crop height and biomass dry weight. The effect was slightly improved by P-fertilizer application, but decreased as the water stress level increased. With or without P fertilizer, Tithonia diversifolia was more effective than Gliricidia sepium, when water was sufficient. At slightly water stress condition, the different between the two OM sources became less significant, especially when P fertilizer was added. Under moderately water stress condition, application of OM and P-fertilizer had no significant impact on maize growth. Keywords: P-availability;P-uptake; sustainable agriculture; water scarcity.